Dayak and Malay Brotherhood in the Malay Collective Memory of Post-Independence Indonesia - Hermansyah, Hermansyah (Al-Albab, 2018)
Each community in the world has a past in which their existence is commonly determined by things happening in their past. To preserve their past a community needs means of transmission, among others, through oral traditions such as stories, mantra, and way of life. They inherit stories, mantra, and ways of life with values that have related meanings to their life. The heritage of these things is very important to preserve and develop the collective identity of the community. As they continue to be passed down, they become the collective memory of a community. The West Kalimantan Malay society has collective memories that are relatively inherited in the form of oral traditions and other life practices such as cultivation. Part of the collective memory has awakened them to the brotherhood with the people called Dayak today. Nevertheless, the collective memory is confronted with challenges both coming from within themselves and from the outside that may eliminate them without a better replacement.